2006
DOI: 10.1002/jmri.20565
|View full text |Cite
|
Sign up to set email alerts
|

A fast and highly automated approach to myocardial motion analysis using phase contrast magnetic resonance imaging

Abstract: Purpose: To develop a fast and highly automated method for calculating two-dimensional myocardial motion and deformation using velocity encoded magnetic resonance imaging. Materials and Methods:Two-dimensional phase contrast magnetic resonance imaging was used to acquire time resolved velocity maps of the myocardium. Cardiac motion was calculated by an iterative integration-regularization scheme of low computational cost. Image segmentation was performed using active appearance models.Results: Validation of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Later noninvasive assessment was made possible using echocardiography (7), tagged MRI (10), displacement encoded (DENSE), and velocity-encoded PC-MRI (11,16,29,30). While tissue Doppler imaging (TDI) has a much higher temporal resolution than PC-MRI, and thus an inherent advantage in determining peak systole, TDI is limited by issues of three-dimensional coverage, operator dependence, and difficulties of obtaining quality images in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Later noninvasive assessment was made possible using echocardiography (7), tagged MRI (10), displacement encoded (DENSE), and velocity-encoded PC-MRI (11,16,29,30). While tissue Doppler imaging (TDI) has a much higher temporal resolution than PC-MRI, and thus an inherent advantage in determining peak systole, TDI is limited by issues of three-dimensional coverage, operator dependence, and difficulties of obtaining quality images in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have used tagged MR imaging to report on myocardial strain (10), this methodology is limited by low spatial and temporal resolution. Investigators found that the phase contrast method is less susceptible to operator interaction and provided higher spatial resolution than tagged MRI (16). While DENSE and velocity-encoded PC-MRI offer equivalent information about transmural regional myocardial strain over the course of the entire cardiac cycle, the former technique's computation of strain from position rather than velocity makes it more susceptible to noise than velocity-encoding modalities (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations